Jenis dan Fungsi Tindak Tutur Unggahan di Grup Facebook Komunitas Pinjaman Online Se-Indonesia - Hana Kartika Lana, Elisabet; Septiani, Dwi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The aim of this research is to describe locutionary, illocutionary and perlocutionary speech acts uploaded to Facebook groups in online loan communities throughout Indonesia. The research method used is descriptive qualitative. The data collection technique for this research is PUP, SBLC and note taking techniques. The data source for this research is primary data in the form of uploads to Facebook groups in online loan communities throughout Indonesia. Based on the results of data analysis, 10 data types of locutionary, illocutionary and perlocutionary speech acts were found in uploads to Facebook groups in online loan communities throughout Indonesia. Types of locutionary, illocutionary and perlocutionary speech acts. Among them are statement locution (2 data), commissive illocution (1 data), directive illocution (3 data), assertive illocution (1 data), directive perlocution (3 data). The functions of speech acts found in Facebook groups of online loan communities throughout Indonesia are statement locution (2 data), threatening commissive illocution (1 data), commanding directive illocution (2 data), advising directive illocution (1 data), assertive assertive illocution (1 data), perlocutionary directive (3 data).